Use of Fluoxetine in Anorexia Nervosa Before and After Weight Restoration. (September 2013) - Sebaaly, Jamielynn C.; Cox, Stephanie; Hughes, Caitlin M.; Kennedy, M. Lindsey Hedgepeth; Garris, Shauna S.
Objective: To examine the evidence for the use of fluoxetine in treatment of underweight and weight-restored patients with anorexia nervosa (AN) and provide recommendations for the clinical usefulness of fluoxetine in AN.Data Sources: Literature was accessed via PubMed through June 2013 using the terms fluoxetine and anorexia nervosa. In addition, reference citations from publications identified were reviewed.Study Selection and Data Extraction: Randomized controlled trials published in English identified from the data sources were evaluated. Studies including the use of fluoxetine in underweight or weight-restored patients with AN were included. Studies of fluoxetine in preclinical animal models of anorexia nervosa were excluded.Data Synthesis: AN is a serious psychiatric illness with no currently approved medication therapy. Because patients with AN frequently display symptoms of major depressive and obsessive-compulsive disorders, medication therapy is commonly used in attempts to improve these symptoms and prevent relapses of AN. Antidepressants such as fluoxetine are the most frequently used medications for these symptoms. The evidence for fluoxetine in the treatment of AN is controversial, particularly in patients who remain underweight. One theory of inefficacy is that underweight patients do not have the nutrients required to make serotonin, therefore preventing selective serotonin reuptake inhibitors from taking effect. Another theory involves dysregulation of the serotonin receptor. Despite the lack of evidence, fluoxetine may still be useful in certain underweight and weight-restored patients.Conclusions: The risk-benefit ratio of fluoxetine in underweight and weight-restored patients with AN is undefined by clinical trials; therefore, clinical experience must be applied for its use in this patient population.